The Effect of Cash Assistance Programs on Children's Involvement in Domestic and Economic Activities in Indonesia - Nur Fikriyah; Dwini Handayani (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the impact of conditional (PKH) and unconditional (UCT/BLT and BLSM) cash assistance programs on children’s participation in work and their working hours in Indonesia using IFLS Wave 5 data, focusing on 2,530 working children aged 5–14 years. Since beneficiary and non-beneficiary households differ in observable characteristics, the analysis addresses potential selection bias and endogeneity through a bivariate probit model that jointly estimates child labor participation and program receipt. The findings indicate that PKH reduces children’s involvement in household chores; however, both PKH and UCT increase the likelihood of children engaging in economic activities, suggesting a shift rather than a reduction in child labor. Cash assistance is also positively associated with longer working hours, particularly among UCT recipients in economic and combined work sectors and PKH recipients in domestic and combined sectors. These effects are more pronounced among girls, older children, and those living in rural or non-Java regions. Overall, the results show that current cash transfer schemes have not fully alleviated household dependence on child labor. Enhancing program effectiveness requires adjustments to benefit adequacy, integration with family economic empowerment initiatives, and regionally responsive policy designs.